2022
DOI: 10.26677/tr1010.2022.1075
|View full text |Cite
|
Sign up to set email alerts
|

Doğrudan Yabancı Yatırımlar ile İhracat Arasındaki İlişki: Türkiye İçin Ampirik Bir Çalışma Relationship Between Foreign Direct Investment and Export: An Empirical Study for Turkey

Abstract: Türkiye, 1980 sonrasında dünyadaki gelişmelere paralel olarak kalkınma politikasını ihracata dayandırmıştır. İhracatın arttırılması bir taraftan yatırım kapasitesinin arttırılmasına, diğer taraftan pazarın genişletilmesine bağlıdır. Sermaye birikimi yetersiz olan Türkiye’nin bu eksikliği gidermekte kullanacağı kaynakların başında doğrudan yabancı yatırımlar gelmektedir. Üretim kapasitesini ve dolayısı ile ihracat hacmini genişletmek için bu kaynağın kullanımını arttırmak gerekmektedir. Bu çalışmada Türkiye’de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…As a result of the study, a long-run relationship was found between the international trade of N-11 countries and both inward FDI and outward FDI. Aztimur and Kaya (2022) examined the relationship between FDI and exports in Turkey between 1970-2019. They examined the cointegration relationship between the two variables with the Fourier SHIN test and found a cointegration relationship between FDI and exports.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a result of the study, a long-run relationship was found between the international trade of N-11 countries and both inward FDI and outward FDI. Aztimur and Kaya (2022) examined the relationship between FDI and exports in Turkey between 1970-2019. They examined the cointegration relationship between the two variables with the Fourier SHIN test and found a cointegration relationship between FDI and exports.…”
Section: Literature Reviewmentioning
confidence: 99%